Desiring to be in touch in a changing communications landscape: Attitudes of older adults. - Lindley, Siân; Harper, Richard; Sellen, Abigail (Proceedings of CHI 2009, 2009)
This paper offers an exploration of the attitudes of older adults to keeping in touch with people who are important to them. We present findings from three focus groups with people from 55 to 81 years of age. Themes emerging from the findings suggest that older adults view the act of keeping in touch as being worthy of time and dedication, but also as being something that needs to be carefully managed within the context of daily life. Communication is seen as a means through which skill should be demonstrated and personality expressed, and is understood in a very different context to the lightweight interaction that is increasingly afforded by new technologies. The themes that emerged are used to elicit a number of design implications and to promote some illustrative design concepts for new communication devices.